Impact of COVID-19 on Healthcare in Humanitarian Settings - Mishra, Kanak (Kathmandu School of Law Review, 2020)
Right to health is a human right available to everyone at all times. However, healthcare under International Humanitarian Law (IHL) is contingent on there being an ‘armed conflict.’ With the world healthcare institutions crumbling with COVID-19 and the worsening humanitarian crisis in many countries, the achievement of universal healthcare stands threatened to its core. In the absence of enough literature, this article attempts to bring out the challenges in the protection of health in complicated humanitarian settings, especially in light of the ongoing pandemic. It also seeks to emphasize that despite the existence of IHL through treaties and Customary International Law, there exists an inability to protect the healthcare professionals in areas of conflict. Further, it also attempts to delve deep into the challenges of access to and protection of public healthcare to the most vulnerable groups in humanitarian settings such as women, children, and refugees. The article concludes by stressing the need to pursue global solidarity to battle the pandemic through building trust and implementing approaches suitable to the needs of all the stakeholders in the humanitarian settings ranging from the perpetrator states, Non-State Armed Groups (NSAGs), civilians, military personnel, to the healthcare professionals involved in administering humanitarian aid.